Tinjauan Atas Persepsi Satuan Kerja Terhadap Rencana Penarikan Dana Pada Satuan Kerja Di Wilayah Kantor Pelayanan Perbendaharaan Negara Jakarta V - Anindya Enggar Novita; Muhammad Heru Akhmadi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
State cash management are government's efforts to maintain state financial liquidity. This study explains about working units and general treasurer of the state (Kuasa BUN) perceptions on Daily Disbursement Plan (daily RPD) conveyment. Daily Disbursement Plan is part of the cash planning process to ensure the amount of government cash funds that are disbursed at certain times. The purpose of this study is to determine the perception of the work unit as budget users and the general treasurer of the state on the submission of daily RPD. This study uses a descriptive qualitative method in which the data collected from the interview process to the working unit partners of KPPN Jakarta V who submitted the Daily RPD in the 2018-2020 budget year. The data processing uses ATLAS.ti software to obtain code codification as research findings. The result of this research shows that working units are understand about daily RPD, whether from urgency, goals, benefit, and creation process aspect of daily RPD.